A potential marker for increased LDL and hypertriglyceridemia risk - K.I.S.N. VAISHNAVI; I. MARIRAJ; N. Krishna GEETHA; Fahad MOHAMMEDAMIN; A. Gowri SHANKAR (Romanian Journal of Medical Practice)
Background and objectives. Serum uric acid (SUA), traditionally associated with gout, is increasingly recognized for its potential role in cardiometabolic disorders, including dyslipidemia. Elevated SUA levels may influence lipid metabolism, thus enhancing cardiovascular disease risk. This study aims to explore the association between SUA levels, dyslipidemia, and related risk factors in a cohort of patients, contributing to a better understanding of their interplay and implications for cardiovascular health. Material and methods. We conducted a retrospective case series involving 30 participants selected from the outpatient Department of General Medicine. The study was approved by the Institutional Review Board, and informed consent was waived due to the retrospective design and use of de-identified data. Participants were aged 18 or older with available data on SUA, LDL cholesterol, and triglycerides, excluding those with a history of gout, renal impairment, or current use of urate-lowering medications. Data were analyzed using descriptive statistics, chi-square tests, and Mann-Whitney U tests, with significance set at p <0.05. Results. The study population had a mean age of 54.7 ± 6.3 years and a mean BMI of 28.4 ± 2.4 kg/m². The mean SUA level was 6.9 ± 0.8 mg/dL, LDL cholesterol was 138 ± 13 mg/dL, and triglycerides were 162 ± 25 mg/dL. Dyslipidemia was present in 60% of the participants. Significant associations were found between hyperuricemia and dietary habits, family history of gout, CVD, and dyslipidemia, as well as the duration of hyperuricemia. Conclusion. Elevated SUA levels are significantly associated with dyslipidemia and other cardiovascular risk factors. The findings suggest the importance of managing SUA levels and lipid profiles concurrently to reduce cardiovascular risks. Further research is needed to explore the long-term cardiovascular outcomes of persistent hyperuricemia and dyslipidemia.